Pengembangan Aplikasi Perhitungan Rancangan Anggaran Biaya Bahan Bangunan Rumah berbasis Android - Loudy Fitria Aspitasari; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
House is a place to live in which isthe construction really needs special attention to make it a dream home. Building a house is not an easy matter for people in general, because building a house requires a lot of costs and needs to be considered. Likewise, the time needed to consider in building a house so that overtime does not occur which also results in over budget. The first problem that occurs is overbudget, namely the existence of an unexpected and excessive reporting expected by the person who is going to build a house and usually that person has previously done a budget calculation manually so that it can produce the results of the calculation manually and the funds actually processing the development process. The second problem that occurs is overtime, namely the existence of construction work time that is past the predetermined time. These problems are also interrelated because the craftsman cannot finish his work according to the desired target will result in overbudget. Likewise, a compilation of people need problems finding the location of the nearest building material store, this takes quite a long time just to find the material. This can also cause overtime because the builders can use 100m2 in a day because searching for the final material can only finish 75m2. To consider this problem the development of a system that aims to make it easier for someone to calculate the cost of building an Android-based home. The results from unit testing, integration testing, validation testing and accuray testing produce 100% valid.